Ultrasonographic Screening of Newborns for Congenital Anomalies of the Kidney and the Urinary Tracts - Tabel, Yilmaz; Haskologlu, Zehra Sule; Karakas, Hakki Muammer; Yakinci, Cengiz (Urology Journal, 2010)
PURPOSE: To search for the efficiency of scanning the newborns with routine urinary system ultrasonography. MATERIALS AND METHODS: Urinary ultrasonography has been carried out on 721 infants born in or brought to our hospital. During the study, name, sex, week of birth, presence of antenatal diagnosis or urinary tract infections, and pathologies in examinations of the babies were recorded. Ultrasonography analysis was done with a scanner by a radiologist. Patients identified to have pathology, were watched closely in pediatric nephrology clinic, and advanced visualizations and treatments were carried out. RESULTS: Seventy-six infants (10.5%) had congenital anomalies of the kidney and the urinary tracts that prompted medical and/or surgical intervention. Of whom, 32 were diagnosed with antenatal ultrasonography and 44 during their initial postnatal ultrasonography screening. The most frequent identified pathology was hydronephrosis, in particular physiologic hydronephrosis (35.8%). The most frequent congenital urinary anomaly which caused hydronephrosis was ureteropelvic obstruction. CONCLUSION: It is suggested to apply the urinary ultrasonography scanning to all the infants that are born or brought to the university hospital. If possible, it is to be considered to include urinary ultrasonography scanning in newborn scanning programs.